Evolution of the fractal dimension for simultaneous coagulation and sintering - Schmid, Hans-Joachim; Al Zaitone, Belal; Artelt, Christian; Peukert, Wolfgang (Chemical Engineering Science, 2006)
Simulation results on the evolution of aggregate structure in aerosol processes with coagulation and sintering as the dominant mechanisms are presented. A model for simulation of the three-dimensional morphology of nano-structured aggregates formed by concurrent coagulation and sintering is applied. The model is based on a stochastic diffusion controlled cluster–cluster aggregation algorithm and sintering is modeled as a successive overlapping of spherical primary particles, which are allowed to grow in order to maintain mass conservation. This leads to computer simulated structured aggregates which are then subject to evaluation. Two different methods to determine the fractal dimension are presented which give comparable results. It is shown that even very small particles show the same fractal behavior. Furthermore, equilibrium structures assuming a constant ratio of the characteristic collision time to the characteristic fusion time are considered as well as the kinetics of structural changes due to a change in the ambient condition
Keywords: Simulation; Sintering; Fractals; Coagulation; Particle formation; Nanostructure